Oral, axillary, and tympanic temperature measurements in older and younger adults with or without fever - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2008)
Objectives The purpose of this study was to compare the results of body temperature obtained by a nurse with standard mercury thermometers from axillary and oral regions with the results of infrared tympanic thermometer in febrile and afebrile patients/in older and younger adults with or without fever, and to determine whether tympanic measures are suitable for use in the elderly population. Methods This study comprises a single-center, randomized, prospective comparison trial. Patients were allocated according to the Australasian National Triage Scale. Patients in triage categories 1 and 2 were excluded from this study. Only individuals aged 18 years and above were included in this study. Each patient was exposed to a constant environmental temperature for 10 min before the administration of simultaneous temperature measurements, which were performed via mouth, right axilla, and tympanic membranes. A record of readings and descriptive informations was made. Results No statistical significance in readings according to the type or place of thermometers according to the age groups (< 65 years/ >= 65 years) or according to fever were observed. Tympanic temperature sensitivity and specificity were high. Conclusion Tympanic thermometers seem to be optimal for use with the elderly population. Owing to the ease of application, safety, and tolerability in the elderly; their use in routine practice seems to be advantageous. Higher reading of tympanic measurements may lead to a suspicion of infection, especially in the elderly, which may be helpful in clinical treatment in this age group. European Journal of Emergency Medicine 15:334-337 (C) 2008 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: axillary; elderly; fever; oral; temperature; tympanic; BODY-TEMPERATURE; ACCURACY; THERMOMETERS